Urban Rail and Sustainable Development Key Lessons from Hong Kong, New York, London and India for Emerging Cities - Sharma, R.; Newman, Peter (2017)
This paper discusses the significance of urban rail in sustainable development in the developing and developed world by examining the cases of Hong Kong, New York, London and Indian cities. The paper analyses the project structuring and financing of the urban rail system in these cities and its contribution to shaping sustainable urban growth and sustainable urban development in general. Observations from the case studies underscore the paper's main emphasis which is that both private and public funded urban rail require innovative financing mechanisms (specifically land based) to sustain or revive themselves financially and that urban rail lends itself to such innovation more than urban road projects as well as multiple other co-benefits. The paper reviews metro projects in several Indian cities and explores the applicability of innovative financing mechanisms and the challenges in adopting them in the Indian context to enable a sustainable urban development model for emerging cities.